Analisis Implementasi Pembelajaran Projek Berbasis Kearifan Lokal di SD - Amalia, Fadhilah Putri; Choirin Attalina, Syailin Nichla (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
This local wisdom-based project learning at SD Negeri 8 Suwawal will be carried out by class 4, to be introduced to what local wisdom exists because currently many students are not familiar with existing local wisdom due to developments over time. This project activity has been determined with the theme of local wisdom where students will gain the development of the values of the Pancasila dimension through various activities in the project. The purpose of writing this article is to describe how the results of the analysis of local wisdom-based project learning through a mini project will be carried out. The design chosen in this research is qualitative where the data produced through a process of observation, interviews, and triangulation documentation will be analyzed into qualitative descriptives. The results of the research obtained show that mini project activities are carried out simply which require collaboration between students as well as strengthening the design of activities by educators which will show changes in the understanding of local wisdom in that not only knowledge increases but independent and creative attitudes can also be achieved. improved from these activities with the hope that educators will also develop mini projects.